Expression, crystallization and preliminary crystallographic analysis of PilZ(XAC1133) from Xanthomonas axonopodis pv. citri - Guzzo, Cristiane R. (International Union of Crystallography, 2009)

(untitled)
Proteins containing PilZ domains are widespread in Gram-negative bacteria and have recently been shown to be involved in the control of biofilm formation, adherence, aggregation, virulence-factor production and motility. Furthermore, some PilZ domains have recently been shown to bind the second messenger bis(3′→5′)cyclic diGMP. Here, the cloning, expression, purification and crystallization of PilZ(XAC1133), a protein consisting of a single PilZ domain from Xanthomonas axonopodis pv. citri, is reported. The closest PilZ(XAC1133) homologues in Pseudomonas aeruginosa and Neisseria meningitidis control type IV pilus function. Recombinant PilZ(XAC1133) containing selenomethionine was crystallized in space group P6(1). The unit-cell parameters were a = 62.125, b = 62.125, c = 83.543 Å. These crystals diffracted to 1.85 Å resolution and a MAD data set was collected at a synchrotron source. The calculated Matthews coefficient suggested the presence of two PilZ(XAC1133) molecules in the asymmetric unit.